Exploring the behavioral patterns transformation of learners in different 3D modeling teaching strategies. (March 2019) - Huang, Tien-Chi; Chen, Mu-Yen; Lin, Chun-Yu
Abstract: 3D modeling is the core technique and the basis of 3D printing which becomes popular in 2010s. To respond the growing needs of industrial community, this study apply the cognitive-apprenticeship strategy using various teaching materials, including three-view diagram and tangible 3D materials, in the 3D modeling course. The lag sequential analysis and interviews are adopted to explore the pattern transformation of the learners' meta-cognition behavior during the problem-solving tasks. The results show that different teaching methods and materials lead to differentiated metacognitive behaviors. Moreover, comparing to traditional instruction strategy, using 3D tangible object in cognitive-apprenticeship instruction stimulates more meta-cognition behaviors, further leads to successful problem-solving. Highlights: Explored students' behavior patterns transformation in a 3D modeling course. Different teaching methods and tools lead to differentiated metacognitive behaviors from students. Metacognitive exploring and experience are key abilities to the modeling process. Cognitive apprenticeship teaching and 3D tangible objects facilitated learning performance.